Upaya Pencegahan Stunting Melalui Kegiatan Gasting (Garahan Bebas Stunting) di Desa Garahan, Kecamatan Silo - Ajeng Pramesthy ardiani Kusuma; Navira Cindy Kartika; Rifqotul Inayat (Compromise Journal Community Proffesional Service Journal, 2024)
Stunting is a chronic nutritional problem that occurs worldwide caused by suboptimal nutritional intake from pregnancy to 24 months or 2 years of age. Stunting in childhood is associated with delays in motor development and lower intelligence levels. Symptoms shown by stunting sufferers include a child's height that is shorter than children of the same age, the child looks smaller for his age, low body weight, and delayed bone growth (Laska et al., 2024). Stunting has short-term and long-term impacts. In the short term, stunting causes depression of immune function, metabolic changes, decreased motor development, low cognitive values, and low academic values (Widjayatri et al., 2020). Meanwhile, the long-term impacts of children with stunting include, when they grow up, they will be at risk of obesity, coronary heart disease, hypertension, osteoporosis, decreased work performance, and productivity (Dekasari & Gunawan, 2024)